2007
DOI: 10.1097/hjh.0b013e3280104dba
|View full text |Cite
|
Sign up to set email alerts
|

Long-term calcium antagonist treatment of human hypertension with mibefradil or amlodipine increases sympathetic nerve activity

Abstract: Mibefradil and amlodipine treatment increase global sympathetic nerve activity similarly during long-term treatment, despite opposite effects on heart rate. Increases in myocardial velocities suggest concomitant cardiac sympathetic activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
0
40
1
1
Order By: Relevance
“…However, another report suggested that amlodipine treatment increases sympathetic nerve activity. 34 In this study, we could not confirm a sympathetic nerve activitydecreasing effect of amlodipine in Dahl salt-sensitive rats.…”
Section: Discussioncontrasting
confidence: 49%
“…However, another report suggested that amlodipine treatment increases sympathetic nerve activity. 34 In this study, we could not confirm a sympathetic nerve activitydecreasing effect of amlodipine in Dahl salt-sensitive rats.…”
Section: Discussioncontrasting
confidence: 49%
“…It has been thought that shortacting CCBs activate the sympathetic nervous system through the baroreflex mechanism, which offsets their favorable effect on IS, such as vasodilation. However, despite its longacting property, amlodipine does not improve IS (11), probably because it activates the sympathetic nervous system (28). On the other hand, the long-acting dihydropyridine CCB, cilnidipine, which suppresses norepinephrine release from sympathetic nerve endings by acting on N-type calcium channel receptors, has been shown to improve IS in subjects with essential hypertension (10) and fructose-fed rats (FFR) (18).…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…More recently, it has been suggested that mibefradil's antihypertensive and vasodilatory effects are mediated by inhibition of L-type VGCC (Moosmang et al 2006). Mibefradil is still the subject of clinical trials where it demonstrates beneficial effects compared to LTCC channel blockers due to its lack of negative chronotropic effects (Lindqvist et al 2007). Although the role of T-type VGCC in regulating blood pressure remains controversial, research into selective T-type channel blockers with potential use in hypertension treatment still continues (Bui et al 2008).…”
Section: Mibefradilmentioning
confidence: 98%